1992
DOI: 10.1143/jjap.31.1899
|View full text |Cite
|
Sign up to set email alerts
|

Thin Films of (BEDT-TTF)2Cu(NCS)2 Prepared by an Electrodeposition Method*

Abstract: Thin films of (BEDT-TTF)2Cu(NCS)2 are prepared by the electrochemical oxidation of BEDT-TTF at a large current density. The films are composed of numerous platelets, which are set on edge and loosely packed on the anodes. The X-ray diffraction suggests that the product contains both amorphous regions and κ-type and other crystals. The ESR and conductivity are discussed in terms of the presence of amorphous regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The -(BEDT-TTF) 2 Cu(NCS) 2 phase, (BEDT-TTF: bis(ethylenedithio)tetrathiafulvalene) prepared as single crystals in 1988, has been intensively studied because it was the first molecule-based superconductor to exhibit a critical temperature higher than 10 K [1]. From the 1990s, thin films [2] and nanorod arrays [3] of -(BEDT-TTF) 2 Cu(NCS) 2 have also been reported. Some of us have shown that roughly spherical nanoparticles of molecule-based conductors could be prepared either by a chemical or an electrochemical route by adding to the solution a growth controlling agent, such as an amphiphilic molecule, an ionic liquid or a long alkyl-chain quaternary ammonium salt [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The -(BEDT-TTF) 2 Cu(NCS) 2 phase, (BEDT-TTF: bis(ethylenedithio)tetrathiafulvalene) prepared as single crystals in 1988, has been intensively studied because it was the first molecule-based superconductor to exhibit a critical temperature higher than 10 K [1]. From the 1990s, thin films [2] and nanorod arrays [3] of -(BEDT-TTF) 2 Cu(NCS) 2 have also been reported. Some of us have shown that roughly spherical nanoparticles of molecule-based conductors could be prepared either by a chemical or an electrochemical route by adding to the solution a growth controlling agent, such as an amphiphilic molecule, an ionic liquid or a long alkyl-chain quaternary ammonium salt [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, thin films of (BEDT-TTF)2Cu(NCS)2 have been grown on indium tin oxide glass, used as the anode [2]. Films are made of plate crystals with sizes of several micrometers and exhibit a semiconducting behavior.…”
Section: Introductionmentioning
confidence: 99%